Dark water rising - Sala, Sharon (Mira, 2019)
Sam and Haley Quaid buried their ten-year-old son and then ended their marriage, all in one week. It wasn<U+2019>t a volatile divorce, but three years later, except for trading Christmas cards, Sam and Haley have completely lost touch<U+2026>until a dramatic weather report sets their paths on a collision course once more. Tropical Storm Gladys is heading straight toward coastal Texas, and locals are anxious as they prepare for potential devastation. Haley, a Realtor, has an appointment to show a property and is determined to keep it, but a hurricane isn<U+2019>t the only looming danger: news reports talk of two prisoners who<U+2019>ve escaped from a nearby penitentiary only a few miles from the house Haley<U+2019>s headed for. When Sam<U+2019>s phone rings with his ex-wife<U+2019>s number, he immediately remembers the card he gave her when they parted on the courthouse steps. If you ever need me, call and I<U+2019>ll be there. She hasn<U+2019>t called in three years, and Sam is sure this can mean only one thing: Haley is in danger, and it<U+2019>s up to him to save her.